Influence of storage conditions on pharmaceutical equivalence and similarity of hydrochlorothiazide tablets - Brevedan, Marta Ingrid Victoria (2022)
Similarity studies are used with the intention to establish interchangeability of certain formulations in vitro, without the need to carry out in vivo studies. This interchangeability between formulations should be conserved during the product shelf life, as an integral part of the pharmaceutical stability. Hydrochlorothiazide (HCTZ), a widely used diuretic, is classified as a class 3 drug in the Biopharmaceutics Classification System (BCS). An immediate-release (IR) solid oral formulation containing a class 3 drug is a candidate for biowaiver if it meets the requirement of ῾very rapid dissolution’ (i.e., ≥ 85% dissolved within 15 minutes). This research aimed to compare four solid oral IR HCTZ formulations (50 mg), commercially available in Argentina, with respect to pharmaceutical similarity and stability. To assess for similarity, dissolution profiles were compared both at time zero (T0) and after 12 months of storage (T12) at pH 1.2, 4.5, and 6.8. To assess for stability, critical quality attributes (CQAs) of the samples were evaluated at T12 of storage (25 °C, 60% relative humidity). At T12, all samples met the requirements for CQAs (i.e., assay, friability, disintegration, uniformity, and dissolution). The reference formulation had the fastest dissolution rate, and sample D was the slowest. Two multisource formulations exhibited statistical differences with respect to the reference sample, both at T0 and T12. Because the evaluated multisource formulations did not meet criteria for very rapid dissolution, they are not candidates for biowaivers. In terms of stability, some statistical differences were detected between dissolution performance at T0 and T12 (for some samples and dissolution media), but no specific pattern could be detected. Thus, it can be considered that the storage conditions did not affect the critical quality attributes of evaluated samples, and their pharmaceutical equivalence was maintained.